Influence of Pectolytic Enzymes and Selected Yeast Strains on the Chemical Composition of Blackberry Wines - Tomić Antonija; Žulj Marin Mihaljević; Andabaka Željko; Tomaz Ivana; Jakobović Snježana; Jeromel Ana (Polish Journal of Food and Nutrition Sciences)
The aim of this study was to determine concentrations of individual o rganic acids, polyphenolic and aromatic compounds in blackberry wine, and to define the influence of different yeast strains (Uvaferm BDX and Lalvin 71B) and pectolytic enzymes (L allzyme OE and Lallzyme EX-V) on the chemical composition and quality of the wine. Blackberry wines were produced in five variants, depending on yeasts and enzymes used: BDX OE, BDX EX-V, 71B OE, 71B EX-V, and Control without the addition of selected yeasts and enzymes. All blackberry wine variants were defined by a relatively high sum of organic acids. The citric acid was the predominant one, which concentrations ranged from 5.42 to 7.31 g/L. The concentration of gallic acid ranged from 19 to 37 mg/L and was in dependence of the yeast strain used. The concentration of procyanidin B2 which was the predominant flavan-3-ol compound, ranged from 103 to 117 mg/L, and there were no significant differences between individual wine variants in the experiment. Rutin is the predominant compound in the flavonol group, followed by quercetin-3-O-glucoside. The predominant one among the anthocyanins was cyanidin-3-O-glucoside whose concentrations ranged from 134 to 229 mg/L. According to the obtained results, the yeast strain and pectolytic enzymes had a significant impact on the concentration of individual anthocyanins in the analyzed wines. The predominant group of aromatic compounds was monoterpenes, among which linalool was the most prominent in all of blackberry wine variants, except in Control.